Congenital insensitivity to pain with anhidrosis (CIPA): sebuah artikel dan manajemen anestesi - Ina Karina Putri G. Sugihen (SEHATI: Jurnal Kesehatan, 2022)
Congenital insensitivity to pain with anhidrosis (CIPA) is hereditary sensory and autonomic neuropathies (HSAN) type IV caused by mutations in NTRK1 gene (neurotrophic tyrosine kinase receptor 1) located in chromosome 1q21-22, encoding the tyrosinase domain receptor high affinity nerve growth factor. It is characterized by anhidrosis, insensitivity to painful stimuli and mental retardation. Given their low prevalence from few reported cases, it is important to know its sign and symptomp to be considered in the differential diagnosis. Therapy for CIPA remains unclear. Complication prevention is the only possible treatment of CIPA. In anesthetic management during surgery, those patients should still administred by analgesics for sedation and anxiolytic effects.